2018
DOI: 10.21577/0103-5053.20180206
|View full text |Cite
|
Sign up to set email alerts
|

Reduction Potential of RuIII-Based Complexes with Potential Antitumor Activity and Thermodynamics of their Hydrolysis Reactions and Interactions with Possible Biological Targets: a Theoretical Investigation

Abstract: In this article density functional theory (DFT)-based calculations were employed to investigate the electrochemistry of the antitumor ruthenium complexes trans-tetrachloro(dimethylsulfoxide) imidazole ruthenate(III) (NAMI-A) and trans-[tetrachlorobis(1H-indazole)ruthenate(III)] (KP1019), their hydrolysis products as well as their interactions with biological S-donors and N-donors targets as cysteine, glutathione and guanine nucleobase. The compounds exhibit different electrochemical behavior upon hydrolysis. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
(106 reference statements)
1
1
0
Order By: Relevance
“…Experimental and computed ground- and excited-state reduction potentials are also provided in Figure . The overall agreement between experimental and simulated values (within 0.2 V) corroborates our protocol for the realistic simulation of wavefunctions (employed for the EOS analysis) and modeling solution-state energetics based on the combination of the TPSSh functional and SMD solvation method. , It has been repeatedly shown that the meta-GGA hybrid TPSSh functional can capture the main characteristics of redox events of transition metal complexes in terms of electronic structures and energy changes. , Furthermore, recent computational studies have also pinpointed the superior performance of TPSSh in modeling the reduction potentials of several compounds, and it was considered among the 20 best-performing functionals for barrier heights and binding energies from more than 200 functionals tested …”
Section: Resultssupporting
confidence: 75%
“…Experimental and computed ground- and excited-state reduction potentials are also provided in Figure . The overall agreement between experimental and simulated values (within 0.2 V) corroborates our protocol for the realistic simulation of wavefunctions (employed for the EOS analysis) and modeling solution-state energetics based on the combination of the TPSSh functional and SMD solvation method. , It has been repeatedly shown that the meta-GGA hybrid TPSSh functional can capture the main characteristics of redox events of transition metal complexes in terms of electronic structures and energy changes. , Furthermore, recent computational studies have also pinpointed the superior performance of TPSSh in modeling the reduction potentials of several compounds, and it was considered among the 20 best-performing functionals for barrier heights and binding energies from more than 200 functionals tested …”
Section: Resultssupporting
confidence: 75%
“…The agreement between simulated and measured redox potentials is often within 0.1 V, which is notable, taking into account the wide chemical space covered; the overall charge of the complexes varies from +4 ([Ir(bpy) 3 ] 4+ in the D ox state) to −1 in ([Ir(ppy) 3 ] − in the D red state), both heteroleptic and homoleptic complexes are investigated and the nature and formal charge of the ligands also change from neutral (bpy) to −1 (ppy), which changes to −1 and −2 upon reduction, respectively. Recent computational studies also highlighted the outstanding performance of TPSSh in modeling the reduction potentials of organic species, 58 ruthenium compounds, 59 and molecular water oxidation catalysts 60 and, among the 200 functionals evaluated, it was among the 20 best performing for barrier heights and binding energies as well. 61 When computing excited-state redox potentials, we did not follow the computational protocol of Demissie, Ruud, and Hansen.…”
Section: ■ Results and Discusionmentioning
confidence: 99%